The Relationship of the Role of Parents with Adolescent Delinquency in Kampung Tangah, Nagari Anduring, Padang Pariaman - Siti Fauziah; Jalius Jalius (SPEKTRUM: Jurnal Pendidikan Luar Sekolah (PLS), 2023)
This research is motivated by the high level of juvenile delinquency that occurred in Tangah Nagari Anduriang Village, Padang Pariaman Regency, this is presumably because the role of parents is not carried out properly, it can be said that the role of parents towards children is still low. This study aims to describe the role of parents, describe juvenile delinquency and see the relationship between the role of parents and juvenile delinquency.This type of research is a descriptive correlational research with a quantitative approach. The population of this study were teenagers who lived in Tangah Village with ages from 13 - 18 years, amounting to 48 people and a sample of 50%, namely 24 people with a sampling technique, namely cluster random sampling. The data collection technique used is a questionnaire and the tool used is a questionnaire. The data analysis technique used the percentage formula and the Spearman Rho formula.The results of this study indicate that: 1) Ther role of parents towards children is low; 2) juvenile delinquency that occurs is high; 3) there is a significant relationship between the role of parents and juvenile delinquency in Tangah Nagari Anduring Village, Padang Pariaman Regency. The suggestion of this research is for parents to increase their knowledge and insight on how to educate and implement/apply their role as parents during the growth and development of children so that they can behave in accordance with the norms that have been set and can be accepted in their environment, To community institutions, in order to give warnings or advice to teenagers who commit juvenile delinquency so that the teenager feels deterred, and for further researchers it is expected to be able to conduct research on other factors that mention juvenile delinquency so as to broaden understanding. Keywords:: The Role Of Parents, Juvenile Delinquency